2017
DOI: 10.17957/ijab/15.0379
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Avena sativa Derived Arabinoxylans as Native Biological Response Modifiers in Broilers

Abstract: This study was aimed to assess the immunomodulatory effects of Avena sativa (oat) derived arabinoxylans (AXs) in chickens. The extracted AXs were evaluated for immunological and immunotherapeutic activities against coccidiosis in chickens. Oat derived AXs significantly enhanced (P<0.05) the in vitro and in vivo lympho-proliferative responses to T-cell mitogens in chicken. Moreover, significantly higher (P<0.05) humoral immune retorts in terms of antibody titres (GMT) to sheep red blood cells (SRBCs), Newcastle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The higher humoral immune responses in barley AXadministered chickens might be due to stimulatory effects of polysaccharides on the classical complement pathway in serum by their interaction with antibodies (43,44). Results of the present study are consistent with previous findings of similar studies that oral administration of sugars resulted in higher antibody titers to SRBCs in chickens artificially inoculated with Eimeria, elevated antibody response to SRBCs in immunocompromised chickens, increased serum antibody responses against SRBCs and Brucella abortus, and increased number of plasma cells in PBLs, enteric leukocytes, and splenocytes (4,36,37,39,45). Results of this study showed higher body weight gains and improved FCRs in chickens administered graded doses of barley AXs as compared to those of the control group.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The higher humoral immune responses in barley AXadministered chickens might be due to stimulatory effects of polysaccharides on the classical complement pathway in serum by their interaction with antibodies (43,44). Results of the present study are consistent with previous findings of similar studies that oral administration of sugars resulted in higher antibody titers to SRBCs in chickens artificially inoculated with Eimeria, elevated antibody response to SRBCs in immunocompromised chickens, increased serum antibody responses against SRBCs and Brucella abortus, and increased number of plasma cells in PBLs, enteric leukocytes, and splenocytes (4,36,37,39,45). Results of this study showed higher body weight gains and improved FCRs in chickens administered graded doses of barley AXs as compared to those of the control group.…”
Section: Discussionsupporting
confidence: 91%
“…Results of this study showed higher body weight gains and improved FCRs in chickens administered graded doses of barley AXs as compared to those of the control group. The improved body weight gains and FCRs in AX-administered birds might be correlated with the ability of AXs to reduce the environmental stress and infectious insults by immunostimulation (37).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation